2006
DOI: 10.1111/j.1467-8624.2006.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Attention to Patterned Stimuli: Developmental Change From 3 to 12 Months of Age

Abstract: To examine the developmental course of look duration as a function of age and stimulus type, 14-to 52-week-old infants were shown static and dynamic versions of faces, Sesame Street material and achromatic patterns for 20 seconds of accumulated looking. Heart rate was recorded during looking and parsed into stimulus orienting, sustained attention, and attention termination phases of attention. Infants' peak look durations indicated that prior to 26 weeks there was a linear decrease with age for all stimuli. Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
236
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(271 citation statements)
references
References 73 publications
(77 reference statements)
32
236
1
2
Order By: Relevance
“…Also, the finding that training led to longer look durations may be seen as surprising given that, in younger (<9-month-old) infants, look duration is negatively associated with long-term cognitive outcomes. However, Courage and colleagues have suggested that voluntary attention control becomes an increasingly important influence on looking behaviour, starting from 12 months, such that increased voluntary attention control is associated with longer look durations towards novel objects (Courage, Reynolds, & Richards, 2006). Thus, increased initial look duration and a faster subsequent fall-off of looks may both be effects of increased endogenous (voluntary) control over orienting behaviours as a result of training.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the finding that training led to longer look durations may be seen as surprising given that, in younger (<9-month-old) infants, look duration is negatively associated with long-term cognitive outcomes. However, Courage and colleagues have suggested that voluntary attention control becomes an increasingly important influence on looking behaviour, starting from 12 months, such that increased voluntary attention control is associated with longer look durations towards novel objects (Courage, Reynolds, & Richards, 2006). Thus, increased initial look duration and a faster subsequent fall-off of looks may both be effects of increased endogenous (voluntary) control over orienting behaviours as a result of training.…”
Section: Discussionmentioning
confidence: 99%
“…The most common measure is the duration of the infant's peak, or longest, look. Behavioral studies with human infants indicate that looking time to both simple and complex stimuli decrease with age until about six months, whereas look durations to more complex stimuli, such as videos and picture of faces, starts to increase starting at around six months (Courage, Reynolds, & Richards, 2006). …”
Section: Running Head: Stress Reactivity and Attention In Infantsmentioning
confidence: 99%
“…By 3 months of age, babies are able to disengage attention from a central stimulus [60], significantly diminishing the time they need to disengage between 4 and 6 months of age [61]. Infants from 6 months of age regulate their attention differently according to whether the stimuli are boring (habituating more rapidly) or engaging (increasing the time they expend looking at it), also reflecting an initial endogenous control of attention [62].…”
Section: Development Of Executive Attention: Behavioral Evidencementioning
confidence: 99%